Depression and Suicide: A Book of Poetry about the Impact of Being Bullied - Jonathan Christian (Institute of Research and Community Outreach - Petra Christian University, 2023)
In this creative work, I want to write a narrative poetry about bullying. Bullying often occurs and goes unnoticed and I want to raise its awareness by writing this book of poetry that revolves around bullying. Bullying has negative impacts on the young and old, such as depression and suicidal thoughts. Depression is a mental illness that affects someone morally and can change their behavior. In this creative work, I want to show the effects of bullying for teenagers, specifically those in high school. The main character, Icha, is bullied due to her social status at school. After being bullied, she becomes depressed and starts to have suicidal thoughts. In the end, she cannot take the pressure anymore and commits suicide. The result is a book of poetry consisting of twenty poems about the story of Icha and her being bullied.